The Drosophila blood–brain barrier invades the nervous system in a GPCR-dependent manner - Contreras, Esteban G.; Kautzmann, Steffen; Klämbt, Christian (Frontiers in Cellular Neuroscience, 2024)
The blood-brain barrier (BBB) represents a crucial interface between the circulatory system and the brain. In Drosophila melanogaster, the BBB is composed of perineurial and subperineurial glial cells. The perineurial glial cells are small mitotically active cells forming the outermost layer of the nervous system and are engaged in nutrient uptake. The subperineurial glial cells form occluding septate junctions to prevent paracellular diffusion of macromolecules into the nervous system. To address whether the subperineurial glia just form a simple barrier or whether they establish specific contacts with both the perineurial glial cells and inner central nervous system (CNS) cells, we undertook a detailed morphological analysis.Using genetically encoded markers alongside with high-resolution laser scanning confocal microscopy and transmission electron microscopy, we identified thin cell processes extending into the perineurial layer and into the CNS cortex. Interestingly, long cell processes were observed reaching the glia ensheathing the neuropil of the central brain. GFP reconstitution experiments highlighted multiple regions of membrane contacts between subperineurial and ensheathing glia. Furthermore, we identify the G-protein-coupled receptor (GPCR) Moody as negative regulator of the growth of subperineurial cell processes. Loss of moody triggered a massive overgrowth of subperineurial cell processes into the CNS cortex and, moreover, affected the polarized localization of the xenobiotic transporter Mdr65. Finally, we found that GPCR signaling, but not septate junction formation, is responsible for controlling membrane overgrowth. Our findings support the notion that the Drosophila BBB is able to bridge the communication gap between circulation and synaptic regions of the brain by long cell processes.